Pulsed Nd:YAG Laser Deposition Of Ruthenium Thin Films - Lee , Wai Keat (2010)
Ruthenium (Ru) is one of the noble air-stable transition metals, which has excellent thermal chemical stability, low electrical resistivity, and relatively high work function near the valence band edge of Si. Recently, Ru has been introduced into the semiconductor industries as a result of the interesting chemical, physical, and electrical properties it possessed.